The effectiveness of the communicative activities applied by teachers of readings and conversation I and II that facilitate the development of oral fluency. case: students of readings and conversation I and II at the Foreign Language Department of the University of El Salvador semester II-2011 - Torres Ramos, Kimberly Alejandrina; Morales Barrientos, Roxana Carolina; Jiménez de Portillo, Susy Maricella; Rosa Flores, Claudia Yanira; Reyes de Amaya, Cecilia; Ricardo Garay Salinas (San Salvador, El Salvador : Universidad de El Salvador, 2012)
Most of people who study English as a second language do it because they want to have the capacity to communicate their ideas, thoughts and feelings not only in a written way, but also in an oral way. However, not all the people have the opportunity to obtain specific levels in the oral skill; this is due to a series of facts that take place during the whole English learning process. Moreover, being their main interest to become proficient in a second language, students place the speaking skill as one of the main goals of study. In order to fulfill the needs of the students, teachers must base their teaching on those communicative activities that best fit on the development of adequate levels of fluency when practicing the language. Along with the process of learning a second language, students need to find many ways of how to develop and improve their oral skill easily. This research has been developed in order to provide information related to the use of communicative strategies, some of them already implemented by some teachers to the students so that they can improve their oral skill. The purpose of getting these activities is to provide other students ways to facilitate the learning of oral communication by putting them into practice.
Anexos: instrumentos de la investigación.
Tesis -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Incluye referencias bibliográficas
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Adquisición de segundo lenguaje -- Pronunciación